2022
DOI: 10.1038/s41598-022-15493-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-time prediction of formation pressure gradient while drilling

Abstract: Accurate real-time pore pressure prediction is crucial especially in drilling operations technically and economically. Its prediction will save costs, time and even the right decisions can be taken before problems occur. The available correlations for pore pressure prediction depend on logging data, formation characteristics, and combination of logging and drilling parameters. The objective of this work is to apply artificial neural networks (ANN) and adaptive neuro-fuzzy inference system (ANFIS) to introduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The number of summation units always equals the number of GRNN output units. The division units only sum the weighted activation of the pattern units without using any activation function (Abdelaal et al 2022;Sadiq and Nashawi 2000).…”
Section: General Regression Neural Network (Grnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of summation units always equals the number of GRNN output units. The division units only sum the weighted activation of the pattern units without using any activation function (Abdelaal et al 2022;Sadiq and Nashawi 2000).…”
Section: General Regression Neural Network (Grnn)mentioning
confidence: 99%
“…Hutomo et al (2019) showed with reasonable accuracy that attributes of seismic amplitude, seismic frequency, acoustic impedance (AI: velocity*density), and shear impedance can be used as parameters to create a model using a neural network. Also, Ahmed et al (2019), Tanko and Bello (2020) and Abdelaal et al (2022) presented a New ANN for Pore Pressure Prediction While Drilling. Also, Mahmoud et al (2020) used machine learning techniques such as ANN and Functional neural networks (FNN) to develop models for estimating Static Young's modulus for sandstone formations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ahmed et al (2019), Tanko and Bello (2020) and Abdelaal et al (2022) presented a New ANN for Pore Pressure Prediction While Drilling. In addition, Mahmoud et al (2020) used machine learning techniques such as ANN and Functional neural networks (FNN) to develop models for estimating Static Young's modulus for sandstone formations.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic data, well logs, and drilling information are required information for determining the pore pressure gradient in a field. In case of a lack of necessary information in a part of the field after screening the available data and preparing the database, the necessary well logs are prepared using estimating models (Abdelaal et al 2022;Haris et al 2017;Jindal and Biswal 2016;Radwan et al 2020;Radwan 2021). Sonic logs can be a good indicator of the internal pressure of the ground.…”
Section: Introductionmentioning
confidence: 99%